2014
DOI: 10.1002/asia.201402575
|View full text |Cite
|
Sign up to set email alerts
|

Metallogel Template Fabrication of pH‐Responsive Copolymer Nanowires Loaded with Silver Nanoparticles and Their Photocatalytic Degradation of Methylene Blue

Abstract: Poly(N,N'-methylenebisacrylamide-4-vinylpyridine) (P(MBA-4VP)) nanowires loaded with silver nanoparticles (Ag NPs) have been fabricated by silver metallogel template copolymerization, and subsequently, silver ions are reduced instead of the template being removed. Ag NPs with a diameter of 5-15 nm were dispersed throughout the core of P(MBA-4VP) nanowires. The size and distribution of the formed Ag NPs could be finely controlled by reduction time. The pH sensitivity of P(MBA-4VP) nanowires offers the possibili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 47 publications
1
15
0
Order By: Relevance
“…Therefore, the size and distribution of the formed Ag NPs could be controlled by reduction time. Different from Ag NPs loaded P(MBA-4VP) nanowires, where Ag NPs were all dispersed throughout the core of the nanowires [29], the formed Ag NPs on P(MBA-AAc) nanowires are inclined to disperse in the whole nanowires and size of the Ag NPs is more smaller under the same reduction condition. However, when the reduction time is further increased to 4 h, the size of the formed Ag NPs greatly increases because of serious agglomeration while the number of Ag NPs on P(MBA-AAc) nanowires decreases due to the leaching of Ag NPs to the reducing agent (showed in Fig.…”
Section: Characterization Of P(mba-aac) 1d Nanostructures and Ag Nps mentioning
confidence: 97%
See 3 more Smart Citations
“…Therefore, the size and distribution of the formed Ag NPs could be controlled by reduction time. Different from Ag NPs loaded P(MBA-4VP) nanowires, where Ag NPs were all dispersed throughout the core of the nanowires [29], the formed Ag NPs on P(MBA-AAc) nanowires are inclined to disperse in the whole nanowires and size of the Ag NPs is more smaller under the same reduction condition. However, when the reduction time is further increased to 4 h, the size of the formed Ag NPs greatly increases because of serious agglomeration while the number of Ag NPs on P(MBA-AAc) nanowires decreases due to the leaching of Ag NPs to the reducing agent (showed in Fig.…”
Section: Characterization Of P(mba-aac) 1d Nanostructures and Ag Nps mentioning
confidence: 97%
“…In our previous research, we have found that Ag NPs loaded P(MBA-4VP) nanowires have highly photocatalytic activity and photostability, and the photodegradation rate of MB is dependent on the content and size of Ag NPs [29]. However, even though the maximum value of the rate constant k for photodegradation of MB catalyzed by Ag NPs loaded P(MBA-4VP) nanowires is still less than the value of photodegradation of MB catalyzed by Ag NPs loaded P(MBA-AAc) nanowires at pH 7.…”
Section: Evaluation Of Photocatalytic Performancementioning
confidence: 99%
See 2 more Smart Citations
“…In addition, PISA has recently been exploited to prepare so‐called nanoworms, an emerging subclass of polymeric nanoparticles with a number of potentially beneficial physical properties such as high surface area and aspect ratio . Due to these unique properties, nanoworms have recently attracted considerable interest in a variety of different fields including catalysis, material science, immunology, tissue engineering, and drug delivery . In addition to nanoworms, amphiphilic block copolymer vesicle structures or polymersomes have been commonly exploited for biomedical applications .…”
Section: Introductionmentioning
confidence: 99%